A qualitative research on medical staff’s cognitive experience of acute skin failure (医护人员对重症患者急性皮肤衰竭认知体验的质性研究) - JI Dandan (季丹丹); HONG Hanhan (洪涵涵); LU Jiaojiao (卢姣姣); CAI Aini (蔡爱旎) (中西医结合护理)
Objective To investigate the medical staff’s cognitive experience of acute skin failure, and understand their knowledge level, attitude and behavior status in clinical practice. Methods Purposive sampling was used to recruit 15 medical staffs in the Intensive Care Unit in a grade-A hospital. The data were collected through semi-structured in-depth interviews, and interview data were analyzed using Colaizzi's 7-step method for thematic data analysis. Results A total of three themes were extracted: the cognitive deficiency and ambiguity in the ASF-associated theories; lack of evidence in nursing of acute skin failure; poor collaboration of multidisciplinary teamwork and need for integration. Conclusion Strategies such as systematically improving the cognitive ability of healthcare professionals, establishing a monitoring and feedback mechanism, developing a standardized management process for acute skin failure, and constructing a multidisciplinary collaborative model should be used to improve the clinical practice of skin care for critically ill patients. (目的 探讨医护人员对重症患者急性皮肤衰竭的认知体验, 了解其在临床实践中的知识水平、态度和行为现状。方法 采用目的抽样法, 选取2024年5月—11月上海市某三级甲等综合性医院重症监护室的医护人员进行访谈, 对符合纳入抽样标准的15名医护人员进行半结构式深入访谈, 采用Colaizzi资料分析原则对资料进行整理分析。结果 共提炼出3个主题: 急性皮肤衰竭的认知不足与理论模糊、医护人员对急性皮肤衰竭护理缺乏依据、跨学科协作的断裂与整合需求。结论 应通过系统性提升医护人员认知能力, 建立监测和反馈机制, 制订急性皮肤衰竭标准化管理流程, 构建多学科协作模式等策略, 以提高重症患者皮肤护理临床实践。)